Pengembangan Sistem E-Office Menggunakan Metode Rapid Application Development - Imani, Fikri Muhaffizh; Saf, Maksum Ro’is Adin (TIN: Terapan Informatika Nusantara, 2025)
Manual handling of correspondence services using physical documents and informal communication platforms such as WhatsApp remains a common challenge in improving the efficiency and transparency of public sector administration. This condition was also identified at a government-affiliated educational institution, LLDIKTI Region XVII, where traditional processes have led to inefficiencies and limited transparency in administrative interactions with higher education institutions. This study aims to design and develop an E-Office system featuring customizable service request forms, dynamic disposition workflows, and a clearly documented approval history. The system was developed using the Rapid Application Development (RAD) method, which encourages active user involvement throughout the development cycle to ensure that the final product aligns with user needs and can be delivered within a shorter timeframe. The results indicate that the system improves service management by centralizing the submission, approval, and delivery of official correspondence into a single integrated platform. The disposition process also becomes more transparent, allowing universities to track the status of their submissions in real time. In addition, the ability to adjust forms and workflows without modifying the system’s source code makes it highly adaptable to changes in business processes. Black box testing on 10 key functions showed a 100% success rate, confirming the system’s functional reliability.